2020
DOI: 10.1016/j.colegn.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Why do nurses miss infection control activities? A qualitative study

Abstract: Background: Hospital acquired infections (HAIs) increase length of hospital stay and lead to poorer clinical outcomes. HAIs are viewed as preventable through risk monitoring and prevention of transmission. These activities are frequently missed. This study explores missed infection control activities through the lens of missed or rationed care. Aim: To determine the factors that contribute to infection control activities being missed. Methods: Semi-structured interviews were conducted with eleven nurses with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(78 citation statements)
references
References 31 publications
1
77
0
Order By: Relevance
“…It is well accepted that the clinical environment plays a role in the transmission of infections such as multi-drug resistant organisms (MDROs) and healthcare associated infections (HCAIs) [ 2 , 7 , 8 , 12 , 14 , 15 , [17] , [18] , [19] , [20] ]. Ineffective cleaning practices by nursing and midwifery staff may also contribute to a high pathogen-load being present within hospital settings [ 15 , 19 , 21 ]. As an important first step to improving environmental hygiene, this study found that nurses and midwives broadly stated that they understood the importance of cleaning, albeit, there is variation in cleaning responsibilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well accepted that the clinical environment plays a role in the transmission of infections such as multi-drug resistant organisms (MDROs) and healthcare associated infections (HCAIs) [ 2 , 7 , 8 , 12 , 14 , 15 , [17] , [18] , [19] , [20] ]. Ineffective cleaning practices by nursing and midwifery staff may also contribute to a high pathogen-load being present within hospital settings [ 15 , 19 , 21 ]. As an important first step to improving environmental hygiene, this study found that nurses and midwives broadly stated that they understood the importance of cleaning, albeit, there is variation in cleaning responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] of VRE transmission pathways within an intensive care unit identified the key role shared medical equipment has in ICU. Factors for suboptimal cleaning of shared equipment may include insufficient stocks of equipment to allow for cleaning and rotation between patients, lack of product at the point of use and perceived lack of time [ 1 , 7 , 19 ]. Understanding reasons for this are important and we will be following this up in future work.…”
Section: Discussionmentioning
confidence: 99%
“…The Missed Nursing Care in Infection Prevention and Control Survey (MNC‐IPC) was developed by Henderson, Blackman, Willis and Roderick at Flinders University in 2017 (Henderson et al, 2019). The survey is composed of three sections, two of which use sub‐scales.…”
Section: Methodsmentioning
confidence: 99%
“…Items for the Missed Nursing Care in Infection Prevention and Control Survey were developed through eleven interviews with Australian infection control experts who were asked to identify the infection prevention activities they believed were missed and the reasons for their omission (Henderson, Willis, Roderick, Bail, & Brideson, 2019). Analysis of the interview data led to the identification of 37 discrete tasks that were viewed as being omitted and 24 reasons why they are omitted.…”
Section: Introductionmentioning
confidence: 99%
“…The results confirmed that these instruments are valid and reliable and therefore can be used for measuring these concepts in different countries. Interestingly, one of these looked at the translated version of an instrument developed to measure missed nursing care in infection prevention and control, which is the first attempt at developing a more focused tool beyond the generic approach to missed nursing care (Henderson, Willis, Roderick, Bail, & Brideson, 2019). This advances our thinking around missed or rationed care and suggests that generic instruments for measuring the concepts may not capture the intricacies of specialist nursing practice.…”
Section: What Does This Special Issue Add?mentioning
confidence: 99%